Knowledge Management in Indian Higher Education – Issues and Challenges - Arun Kumar, A. (Prabandhan: Indian Journal of Management, 2023)
Purpose : The current research focused on knowledge management in Indian higher education. Knowledge management is an important aspect of higher education, as it helps institutions to effectively manage and share knowledge to enhance teaching, learning, and research outcomes. In the context of Indian higher education, there are several policy implications that can help to improve the effectiveness of knowledge management. Methodology : The research paper was prepared based on secondary data. These include creating a comprehensive knowledge management framework, encouraging collaboration among institutions, investing in technology infrastructure, fostering a culture of knowledge sharing, and supporting open access to research publications and educational resources. Findings : I found that knowledge management in Indian higher education requires a multi-faceted approach that involves policy support, technological investments, and a culture of collaboration and knowledge sharing. As the Government of India welcomes foreign universities, the significance of knowledge management becomes even more vital. Implementing these policy implications can help to improve the effectiveness of KM in Indian higher education and support the development of a more robust knowledge-based economy. Practical Implications : It is recommended that the government framework should also include guidelines for the development and implementation of knowledge management systems in higher education institutions. Collaboration among institutions is essential for effective knowledge management. The government should encourage institutions to collaborate with each other to share knowledge and resources. This can be done by creating networks or consortia of institutions that work together on specific projects or initiatives. Originality : Unlike prior research on knowledge management, the current work is to provide a comprehensive understanding of KM in higher education across various mediums.